The impact of attitude toward peer interaction on middle school students' problem-solving self-efficacy during the COVID-19 pandemic - An, Xin; Hong, Jon-Chao; Li, Yushun; Zhou, Ying (Frontiers in Psychology, 2022)
The outbreak of the COVID-19 epidemic has promoted the popularity of online learning, but has also exposed some problems, such as a lack of interaction, resulting in loneliness. Against this background, students’ attitudes towards peer interaction may have become even more important. In order to explore the impact of attitude towards peer interaction on students' mindset including online learning motivation and critical thinking practice that could affect their problem-solving self-efficacy during the COVID-19 pandemic, we developed and administered a questionnaire, receiving 1,596 valid responses. The reliability and validity of the questionnaire were re-tested, and structural equation modeling was applied. It was found that attitude towards peer interaction could positively predict middle school students’ online learning motivation and critical thinking. Learning motivation and critical thinking also positively supported problem-solving self-efficacy. It is expected that the results of this study can be a reference for teachers to adopt student-centered online learning in problem solving courses.